Integrating Palliative Care by Virtue of Diplomacy; A Cross-sectional Group Interview Study of the Roles and Attitudes of Palliative Care Professionals to Further Integrate Palliative Care in Europe - Jelle van Gurp; Jeroen van Wijngaarden; Sheila Payne; Lukas Radbruch; Karen van Beek; Ágnes Csikós; Marlieke Herder-Van der Eerden; Jeroen Hasselaar; InSup-C (FP7) Research Consortium (International Journal of Health Policy and Management, 2022)
BackgroundPalliative care involves the care for patients with severe and advanced diseases with a focus on quality of life and symptom management. Integration of palliative care with curative and/or chronic care is expected to lead to better results in terms of quality of life and reduced costs. Although initiatives in different countries in Europe choose different structures to integrate care, they face similar challenges when it comes to creating trust and aligning visions, cultures and professional values. This paper sets out to answer the following research question: what roles and attitudes do palliative care professionals need to adopt to further integrate palliative care in Europe? MethodsAs part of the European Union (EU)-funded research project InSup-C (Integrated Supportive and Palliative Care). (2012-2016), 19 semi-structured group interviews with 136 (palliative) care professionals in 5 European countries (Germany, the United Kingdom, Belgium, the Netherlands, Hungary) were conducted. A thematic analysis was conducted. ResultsIntegration of palliative care calls for diplomatic professionals that can bring a cultural shift: to get palliative care, with its particular focus on the four dimensions (physical, psychological, social, spiritual), integrated into historically established medical procedures and guidelines. This requires (a) to find an entrance (for telling a normative story), and (b) to maintain and deepen relationships (in order to build trust). It means using the appropriate words and sending a univocal team message to patients and being grateful, modest, and aiming for a quiet revolution with curation oriented healthcare professionals. ConclusionDiplomacy appears to be essential to palliative care providers for realizing trust and what can be defined as normative integration between palliative and curative and/or chronic medicine. It requires a practical wisdom about the culture and goals of regular care, as well as keeping a middle road between assimilating with values in regular medicine and standing up for the basic values central to palliative care.